Environmental Impact and Speciation Analysis of Chemical Mechanical Planarization (CMP) Waste Following GaAs Polishing. (15th August 2017) - Crawford, Steven; Aravamudhan, Shyam
Abstract : Chemical Mechanical Planarization (CMP) is a key enabling process used in semiconductor manufacturing to achieve planarization. Contemporary CMP process use nanoparticle slurries for the chemical and mechanical removal of material. As traditional silicon nears its scaling limits, next-generation devices may require the use of III-V materials such as Gallium Arsenide (GaAs). CMP of GaAs may increase Ga and As levels in wastewater, influencing the potential for environmental safety and health (ESH) concerns. Little is known about the environmental fate, behavior, and biological impact of this waste. In this work, we report on the ESH impacts of GaAs CMP waste, specifically on the (a) presence and speciation of Arsenic in the wastewater effluent; (b) physicochemical properties of the slurry nanoparticles and removed material after polishing; and (c) effect of collected CMP wastes on human health, primarily cytotoxicity.